An Elementary Theory of Endogenous Technical Change and Wage Inequality - Jonas Loebbing (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper presents general results on the effect of endogenous technical change on relative wages in a simple general equilibrium model that covers several more elaborate models of technology choice. The results are based on a simple and intuitive notion of complementarity between technology and labor inputs, and characterize necessary and sufficient conditions for central results from the literature on endogenous technical change. The developed theory generalizes existing work to technologies that are not purely factor-augmenting, production functions that are not differentiable in technology, and settings with more than two (and potentially infinitely many) different types of labor. Applying the theory to assignment models of the labor market, the paper derives new results on the endogenous determination of automation technology, both in a closed economy and in a two country setting with international trade, and sketches directions for future research on endogenous technical change in assignment models.
Keywords: J24; J31; O33; 330; Endogenous Technical Change; Wage Inequality; Factor Demand; Automation; Assignment Model; Monotone Comparative Statics